Position-based multicast routing in mobile ad hoc networks - Qabajeh, Mohammad M.; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Qabajeh, Liana K. (2012)
Nowadays, group communications over Mobile Ad hoc Networks (MANETs) have received significant attention. Multicasting plays an important role in simultaneous delivery of information to group of receivers. Meanwhile, multimedia and real-time applications are becoming essential needs for MANET users. Thus, it is necessary to design efficient and effective multicast routing protocol to support this type of applications. Several efforts have been put to improve Quality of Service (QoS) multicast routing. However, they do not consider scalability issue. This paper introduces a position-based QoS multicast routing protocol (PBQMRP). The main objective of this protocol is to design a lightweight scalable QoS multicast routing scheme irrespective of the number of multicast members and network size. To achieve this, virtual clustering strategy has been introduced. This strategy based on partitioning the network into hexagonal cells and each cell is represented by one powerful node. The proposed scheme eliminates the duplicate packets between cells and reduces the number of participating nodes. Simulation results show that PBQMRP offers higher packet delivery ratio with significantly low overhead compared to ODMRP Protocol.